PENGARUH KONSELING TERHADAP PENINGKATAN PENGETAHUAN, SIKAP, DAN PERILAKU MASYARAKAT TENTANG KESEHATAN LINGKUNGAN - Gamelia, Elviera; Kurniawan, Arif; Widiyanto, Agnes Fitria (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2015)
Rural communities in Puskesmas I dan II Baturaden have environmental health problems . Health education can be used to address environmental health problems by changing people's behavior. Health councelling given by an expert, to the individual to overcome the problem. Researchers wanted to determine the effect of health counseling on knowledge, attitudes, and behaviors in the community about environmental health Puskesmas I and II Baturaden Banyumas. This type of research is a quasi experimental study to design one group pre -test and post-test design . Sample of reseach using purposive sampling. The sample was 37 people . Analysis of the data used was the Wilcoxon test . The variables measured were knowledge , attitudes , and behavior of environmental health . The study says that health counseling can improve knowledge , attitudes and behavior about environmental health . Advice can be given that the provision of health education to the community should use counseling methods , because this method is more effective and striking the individual .